Introduction to Magic E in Reading English Words CVCe - Ni Luh Desy Suari Dewi; I Gede Neil Prajamukti Wardana (CV. Publikasi Indonesia, 2024)
English vowels consist of five letters that have different pronunciations (sounds) in English words. There are 20 vowel sounds and 24 consonant sounds in English. It is a challenge for English teachers to teach English learners the concept of reading English words. English vowels with the symbols a, i, u, e, and o have different pronunciations when they are positioned between consonants in the word CVC and when the word CVC is added by the letter e in the word CVCe. Therefore, this paper analyzed the influence of the letter e (which is referred to as magic e) in the pronunciation of English vowel sounds. This research is qualitative research with documentation study methods to analyze and explain how the vowel sounds are pronounced in CVC and CVCe words so that English reading teaching steps are obtained that are easy to understand. The results showed that English vowels were pronounced as short vowel sounds in CVC words and pronounced as long vowel sounds in CVCe words. The steps to teach magic e that can be applied are to repeat the short vowel sound material, introduce the concept of sounds and letters, introduce the concept of short and long vowel sounds, read two words similar in the concept of CVC and CVCe, and practice reading the word CVCe regularly.